O tempo que nos resta: estudos Kamaiurá - Faggiano, Daniel Lopes (2014)
In our transition process to the production and reproduction of capital mode through a colonial via, we plated a particular colonial capitalism in the tropics. Colonial, since it develops itself in atrophy, not completely, keeping and reinforcing Brazil as an subaltern bond of the imperialism. Considering the particularity of each author, I remark the works of Caio Prado Jr., Francisco Oliveira, Florestan Fernandes, José Chasin, Octavio Ianni e Maurício Tragtenberg as fundamentals in the marxist formulation of the Brazilian thoughts. The current work starts from The Brazilian March to West, searching our historical particularity. Moved by a late industrialization of the country, the myth of development takes violently all Brazilian people to be submitted to this cause, while the profits pass to be concentrated, even more, in the hands of farmers, national and international dealers. The domination of value of change by the value of use, contradictory present in the products of capitalist civilization, together with the transformation of lands to capital- private property, reaches the limits of Parque Indígena do Xingu (MT) and, slowly, charmingly penetrates the daily life of the aldeias. Considering the studies made since 1965 by the anthropologist Carmen Junqueira, this work intends to critically analyze the arriving of the goods with its values and of the capital-social relation in the aldeia Kamaiurá from Ipavu, analyzing the way the sociability of capital breaks up the existing collectivity, besides pointing out the arrangements and adjustments made by the Kamaiurá when facing the destructive process of our colonial capitalism. This work, contemporary to the capital s crisis era, searches to confront the Brazilian reality without loosing its human horizon, ontological. At last, it defends that the Kamaiurá s way of life, anchored in the collective element of their land, may be put, humanly, against the capital and open, consciously, free paths among the rubble of the amplified production and reproduction of life under the capital